Boron-doped diamond MOSFETs operating at temperatures up to 400°C - Jiangwei Liu; Tokuyuki Teraji; Bo Da; Yasuo Koide (Functional Diamond)
The boron-doped diamond (B-diamond) metal-oxide–semiconductor field–effect transistors (MOSFETs) are fabricated and characterized at operating temperatures up to 400°C. The SiO2 serves as the gate oxide insulator, while the Ti/Pt bilayer is employed as the gate contact metal. As the operating temperature rises from room temperature (RT) to 400°C, the absolute drain current maximum for the B-diamond MOSFET increases from 3.9 μA mm−1 to 177.4 μA mm−1. Conversely, the on-resistance decreases significantly from 1469.8 kΩ mm to 16.5 kΩ mm. The on/off ratio for the MOSFET at RT is 1.9 × 105, which increases to over 5.0 × 106 at temperatures exceeding 100°C. The threshold voltage exhibits a decreasing trend, though it deviates from this trend at 300°C. The subthreshold voltage and extrinsic transconductance maximum show increasing trends from 113 mV dec−1 to 299 mV dec−1 and from 0.9 μS mm−1 to 23.1 μS mm−1, respectively. The interfacial trapped charge density is found to be stable in the range of 8.0 × 1011–2.3 × 1012 eV−1 cm−2.